2018
DOI: 10.1111/febs.14612
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies reveal the molecular mechanism of PETase

Abstract: Poly(ethylene terephthalate) (PET) is a class of plastic material widely used in modern society, but large amounts of PET waste cause severe environmental problems. Obtained from a PET-consuming bacterium Ideonella sakaiensis, the enzyme PETase exhibits superb hydrolytic activity and substrate preference toward PET. Here, we summarize some recent advances in the crystallographic analysis of PETase. These reports uncover structural features of PETase that are involved in its catalytic activity. In comparison to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
139
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 23 publications
7
139
0
1
Order By: Relevance
“…In addition, it has a wider substrate binding groove compared to cutinases. Since the majority of amino acids forming the substrate binding groove are conserved among homologous enzymes, this difference has been attributed to different factors, among which is the increased mobility of a conserved tryptophan residue, which is only observed in the PETase structure [68]. A neighboring serine (which corresponds to histidine in homologous structures) allows for the increased mobility of this tryptophan, which is crucial for substrate binding.…”
Section: Structural Determinants Of Cutinase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has a wider substrate binding groove compared to cutinases. Since the majority of amino acids forming the substrate binding groove are conserved among homologous enzymes, this difference has been attributed to different factors, among which is the increased mobility of a conserved tryptophan residue, which is only observed in the PETase structure [68]. A neighboring serine (which corresponds to histidine in homologous structures) allows for the increased mobility of this tryptophan, which is crucial for substrate binding.…”
Section: Structural Determinants Of Cutinase Activitymentioning
confidence: 99%
“…One of these loops, the one harboring the catalytic base, named β8-α6 loop, is longer in PETases. It has been suggested that the additional DS bond is required to maintain the catalytic triad, and the extended loop to their functional locations [68]. In addition, a PETase variant without this DS bond had a significantly higher T m compared to WT (46.8 vs 33.6 • C), indicating the importance of this bond for the thermostability of the enzyme [65].…”
Section: Structural Determinants Of Cutinase Activitymentioning
confidence: 99%
“…This enzyme outcompetes other cutinases for the hydrolysis of crystalline PET at 30 • C as demonstrated in a comparative study with the leaf-branch compost cutinase (LCC) and a cutinase from the Thermobifida group (Yoshida et al, 2016). The elucidation of PETase three-dimensional structures by different groups (Han et al, 2017;Austin et al, 2018;Chen et al, 2018;Joo et al, 2018;Liu B. et al, 2018;Palm et al, 2019), lead to a proposal for the degradation mechanism and structural hallmarks responsible for superior activity as reviewed by Taniguchi et al (2019). Structural features compared to other cutinase structures include an additional disulfide bond for improved stability at the position of the active site histidine, allowing for increased flexibility of the adjacent extended loop region (Fecker et al, 2018), thus facilitating the interaction with the polymer (Joo et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Follow-up investigations of PETase have determined its structure by X-ray crystallography and identified significant amino acid residues for activity, as well as made initial attempts to enhance activity (Han et al, 2017;Joo et al, 2018;Austin et al, 2018;Fecker et al, 2018;Liu et al, 2018;Chen et al, 2018;Ma et al, 2018). PET degradation using heterologously expressed PETase has been successfully shown in a variety of microorganisms, including in E. coli (Seo et al, 2019), B. subtilis (Huang et al, 2018), yeast (P. pastoris) (Z.…”
Section: Introductionmentioning
confidence: 99%